Edukasi Pemanfaatan Limbah Plastik di Perairan Pesisir Kepada Pemuda Desa Paya Peunaga Kabupaten Aceh Barat - Risma, Okta Rabiana; Rahmi, Mira Mauliza (SEURAYA Jurnal Pengabdian Kepada Masyarakat, 2025)
Plastic waste is a threat to the sustainability of biological natural resources today. Various efforts have been made by local governments, both central and regional, in managing this waste. One of the activities of waste utilization can be through education and processing. The purpose of this community service activity is to educate the youth community of Paya Peunaga Village about the dangers of waste to the environment, coastal ecosystems and humans, as well as provide counseling on the use of plastic waste that can have economic value. The methods used in this activity are counseling and demonstration. Educational activities utilize plastic waste from surrounding coastal areas into recyclables such as plastic waste into flowers and keychains. This activity does not significantly reduce the volume of waste, but can increase innovation, creative ideas, and build good social relationships. Keywords : Waste, Utilization, West Aceh